Distracted mobile device use among street-crossing college student pedestrians: an observational approach. Issue 7 (3rd October 2022) - Piazza, Andrew J.; Knowlden, Adam P.; Hibberd, Elizabeth; Leeper, James; Paschal, Angelia M.; Usdan, Stuart
Abstract: Objective To estimate the incidence of mobile device use among street-crossing pedestrians and explore differences by sex and intersection type at a large public South-eastern university in the United States. Participants All instances of campus pedestrians crossing the street during the observation period ( N = 4, 878). Methods Video recordings of crosswalk activity at four locations were analyzed for pedestrian use of a mobile device while crossing. Results Device use while crossing was observed 1, 201 (24.6%) times. Of male crossing instances, 277 (16.8%) were coded as using a device. Of female instances, 924 (28.6%) were coded as using a device. Differences in device use while crossing were found between sexes and some intersection types. Conclusions This study estimates mobile device use while crossing the street and suggests differences by sex and intersection type. Future research should focus on improving understanding of the problem and evaluation of interventions to address the issue.